2017
DOI: 10.1038/s41598-017-15257-0
|View full text |Cite|
|
Sign up to set email alerts
|

A Study on Image Quality in Polarization-Resolved Second Harmonic Generation Microscopy

Abstract: Second harmonic generation (SHG) microscopy represents a very powerful tool for tissue characterization. Polarization-resolved SHG (PSHG) microscopy extends the potential of SHG, by exploiting the dependence of SHG signals on the polarization state of the excitation beam. Among others, this dependence translates to the fact that SHG images collected under different polarization configurations exhibit distinct characteristics in terms of content and appearance. These characteristics hold deep implications over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…This configuration does not yield a pure circular polarized beam after the objective due to ellipticity introduced by the various optical elements inside the microscope. Although circular polarization is typically preferred in SHG imaging experiments as it is considered that this illumination configuration does not discriminate between collagen fibrils aligned differently it was previously shown that an elliptically polarized laser beam can in some scenarios be better than a circularly polarized beam in terms of image quality [31], and therefore we consider that a circular polarization is not necessarily preferable to an elliptical one.…”
Section: The Nonlinear Optical Microscopementioning
confidence: 97%
“…This configuration does not yield a pure circular polarized beam after the objective due to ellipticity introduced by the various optical elements inside the microscope. Although circular polarization is typically preferred in SHG imaging experiments as it is considered that this illumination configuration does not discriminate between collagen fibrils aligned differently it was previously shown that an elliptically polarized laser beam can in some scenarios be better than a circularly polarized beam in terms of image quality [31], and therefore we consider that a circular polarization is not necessarily preferable to an elliptical one.…”
Section: The Nonlinear Optical Microscopementioning
confidence: 97%
“…An example on the utility of the HISTOBREAST image datasets consists in our previous work 32 , where we used part of HISTOBREAST's progressively degraded HSIMs (those collected under 5x magnification) to benchmark a set of Full Reference Image Quality Assessment Algorithms. The evaluation of "blind" image quality assessment algorithms 43 is also possible, considering that the quality level of each progressively degraded HSIM in HISTOBREAST is a priori known.…”
Section: Utilitymentioning
confidence: 99%
“…A Leica HCX PL FLUOTAR 40X/0.75 objective was used for focusing the laser beam on the sample and for collecting the backward-generated MPM signals (Fig. 1, representation adapted from [42]). The average power reaching the sample plane was kept below 15 mW.…”
Section: Image Acquisition and Processingmentioning
confidence: 99%